(untitled) (Innovative professional education, 2022)
The assessment of the quality of professional training of specialists in institutions of professional preliminary higher education should be considered as a logical structure that combines four stages. Tools for evaluating the quality of specialist training should correspond to the objects of evaluation and the characteristics of students. Evaluation criteria should correlate with the goals and tasks of the inspection. A well-founded methodology for assessing competencies and the quality of professional training of specialists in colleges makes it possible to determine the real level of compliance of students’ preparation.